The Forgotten Voices: Enabling Children and Young People With Intellectual Disability to Express Their Views on Their Inpatient Hospital Experience - Jo Wray; Jessica Russell; Faith Gibson; Charlotte Kenten; Kate Oulton (Health Expectations)
ABSTRACT Background The importance of enabling patients to provide feedback on their experience of healthcare is widely accepted but there are few appropriate measures to enable children and young people to directly provide feedback, particularly those with intellectual disability or younger children. Our primary aim was to develop and test patient‐reported experience measures for children and young people with intellectual disability who use inpatient hospital services. A secondary aim was to test these measures with younger children aged 4–7 years without intellectual disability. Methods A hospital inpatient patient‐reported experience measure previously developed for children aged 8–11 years was revised iteratively in conjunction with a parent advisory group (comprising five parents of children and young people with and without intellectual disability) and children and young people with intellectual disability. The final patient‐reported experience measure was tested in children's inpatient wards at seven hospitals in England over a 3‐month period. Results Parents suggested a need for a single patient‐reported experience measure for all children with intellectual disability which contained simpler language, fewer questions and response options, and images to illustrate each question. The final patient‐reported experience measure had 22 questions, each with a corresponding image, and a free text box in which children could add anything further. Questions addressed environment, people, care and treatment and safety. During testing at seven children's hospitals, 52 children and young people with intellectual disability (4–18 years) and 76 children without intellectual disability (4–7 years), all of whom received inpatient care, completed the patient‐reported experience measure. Two percent of data were missing; in 16 instances respondents either ticked two responses or placed a tick between two response categories. Half the respondents added comments and/or drew a picture. Conclusion The development of a patient‐reported experience measure for children and young people with intellectual disability provides a previously unavailable opportunity for them to report on their experiences of inpatient care and have their voices heard. Future work to extend testing to a wider group is underway and will enable us to clarify whether one patient‐reported experience measure is valid and reliable for all children and young people with intellectual disability. Patient or Public Contribution A parent advisory group, comprising parents/carers of young people with or without a learning disability, advised on all aspects of the wider study design and specifically on revisions to the measure reported in this manuscript. The parent advisory group met twice a year during the study with email contact between meetings for specific requests and study updates. Representatives of the advisory group also attended the study steering group.